Agronomic evaluation of seedbed and mulching alternatives with plant spacing for dry‐season fluted pumpkin in coarse‐textured tropical soil. (18th July 2017) - Obalum, Sunday E.; Edeh, Ifeoma G.; Imoh, Odirichi N.; Njoku, Ogechi M.; Uzoh, Ifeyinwa M.; Onyia, Vincent N.; Igwe, Charles A.; Reichert, Jose M.
Abstract: Fluted pumpkin ( Telfairia occidentalis ) has high agronomic and food relevance in the tropics. Production of this vegetable in the dry season with irrigation is increasingly popular and is mostly on droughty soils, thus requiring research on appropriate combination of soil moisture conservation/management practices. This study evaluated the interactions among seedbed configuration (flat and raised), surface mulching (grass‐mulched and no‐mulch) and plant spacing (100 2, 50 2 and 25 2 cm 2, designated wide, intermediate and close spacing, respectively) on fluted pumpkin performance in a sandy‐loam soil in southeastern Nigeria during 2014/2015 dry season. Seedling emergence (ratio of emerged to expected seedlings) was highest and lowest in flat/mulched/wide and flat/no‐mulch/close combinations, respectively. Main effects showed higher seedling emergence in mulched (67.9%) than no‐mulch plots (53.1%) and in wide (70.8%) and intermediate spacing (64.6%) compared to close spacing (46.0%). Fresh leaf yield assessed biweekly during 6–14 weeks after sowing was generally highest and lowest in flat/mulched/close and flat/no‐mulch/wide combinations, respectively. Seedbed configuration had no distinct effect on leaf yield; hence, flat/mulched/close option was similar to raised/mulched/close option. Yields from mulched/wide and no‐mulch/close options were similar with a mean (2735 kg/ha) approximating the overall mean (2868 kg/ha). Flat/mulched/close combination is the best management practice to grow fluted pumpkin with irrigation on droughty soils during the dry season of the tropics. Where this best practice is compromised due to mulch or seed scarcity, the ensuing no‐mulch/close and mulched/wide, respectively can support dry‐season production of pumpkin in droughty tropical soils at average levels. Abstract : Seedbed configuration had no distinct effect on leaf yield; hence, flat/mulched/close was similar to raised/mulched/close whereas yields from mulched/wide and no‐mulch/close options were similar with a mean (2735 kg/ha) approximating the overall mean (2868 kg/ha). Flat/mulched/close combination is the best management practice to grow fluted pumpkin with irrigation on droughty soils during the dry season of the tropics. Where this best practice is compromised due to mulch or seed scarcity, the ensuing no‐mulch/close and mulched/wide, respectively can support dry‐season production of pumpkin in droughty tropical soils at average levels.